How do People with Intellectual Disabilities in Norway Experience the Transition to Retirement and Life as Retirees? - Jeanette Engeland; Anna Kittelsaa; Ellen Melbye Langballe (Scandinavian Journal of Disability Research, 2018)
People with intellectual disabilities have increased life expectancy compared to just a few decades ago, and there is a lack of knowledge about the experiences of transition into retirement for this group. In this study, semi-structured in-depth interviews with seven retirees with intellectual disabilities were conducted in order to investigate their reasons for retirement, experiences of the transition, their activities and satisfaction with their lives as retirees. Data was analysed with systematic text condensation. Most participants described that, although they experienced the retirement process and transition as abrupt, retirement had a positive impact on health, satisfaction and self-determination. Findings in this novel study in a Nordic context are need of increased knowledge on ageing and retirement among people with intellectual disabilities, and that individual guidance might improve their transition into retirement.